2013
DOI: 10.1038/jcbfm.2013.109
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Induces Phenotypic Modulation in Cerebral Vascular Smooth Muscle Cells: Implications for Cerebral Aneurysm Pathology

Abstract: Little is known about vascular smooth muscle cell (SMC) phenotypic modulation in the cerebral circulation or pathogenesis of intracranial aneurysms. Tumor necrosis factor-alpha (TNF-a) has been associated with aneurysms, but potential mechanisms are unclear. Cultured rat cerebral SMCs overexpressing myocardin induced expression of key SMC contractile genes (SM-a-actin, SM-22a, smooth muscle myosin heavy chain), while dominant-negative cells suppressed expression. Tumor necrosis factor-alpha treatment inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 45 publications
8
116
0
Order By: Relevance
“…Myocardin suppression may also regulate the proliferative response to injury because myocardin expression was robust in wild-type animals but nearly absent in IRS-1 Ϫ/Ϫ animals that had a hyperproliferative response to injury, and myocardin is known to modulate this response (31). Other variables, such as TNF␣, PDGF, and oxidized LDL, that regulate VSMC differentiation stimulate KLF-4 expression, thereby resulting in enhancement of VSMC dedifferentiation (30,(32)(33). During vascular injury, KLF-4 is up-regulated, and this is accompanied by dedifferentiation (34 -35).…”
Section: Irs-1 Prevents Vsmc Dedifferentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardin suppression may also regulate the proliferative response to injury because myocardin expression was robust in wild-type animals but nearly absent in IRS-1 Ϫ/Ϫ animals that had a hyperproliferative response to injury, and myocardin is known to modulate this response (31). Other variables, such as TNF␣, PDGF, and oxidized LDL, that regulate VSMC differentiation stimulate KLF-4 expression, thereby resulting in enhancement of VSMC dedifferentiation (30,(32)(33). During vascular injury, KLF-4 is up-regulated, and this is accompanied by dedifferentiation (34 -35).…”
Section: Irs-1 Prevents Vsmc Dedifferentiationmentioning
confidence: 99%
“…This finding was replicated in our study, and we noted an enhanced dedifferentiation response in the absence of IRS-1, suggesting that IRS-1 is also functioning during injury to attenuate smooth muscle cell proliferation by this mechanism. KLF-4 can also be induced by other atherogenic stimuli, such oxidized phospholipids and advanced glycation end products (32)(33)(34)(35)(36).…”
Section: Irs-1 Prevents Vsmc Dedifferentiationmentioning
confidence: 99%
“…A series of in vitro and in vivo studies by the Jefferson group found that the phenotypic modulation of SMCs in CAs was induced by tumor necrosis factor-α (TNF-α). 17,18 Specifically, TNF-α inhibited the contractile phenotype of SMCs and induced proinflammatory/matrixremodeling genes, namely MCP-1, MMPs, vascular cell adhesion molecule 1, and interleukin 1β (IL-1β). 17 This process was mediated by Kruppel-like transcription factor 4, a known regulator of SMC differentiation.…”
Section: Cerebral Aneurysms: An Inflammatory Diseasementioning
confidence: 99%
“…17,18 Specifically, TNF-α inhibited the contractile phenotype of SMCs and induced proinflammatory/matrixremodeling genes, namely MCP-1, MMPs, vascular cell adhesion molecule 1, and interleukin 1β (IL-1β). 17 This process was mediated by Kruppel-like transcription factor 4, a known regulator of SMC differentiation. In a follow-up study, the same group found that phenotypic modulation of SMCs was reversed with a TNF-α inhibitor after aneurysm induction.…”
Section: Cerebral Aneurysms: An Inflammatory Diseasementioning
confidence: 99%
“…[25] TNF-α has been previously identified as a contributor to the phenotypic modulation of VSMCs in vivo following hemodynamic stress. [26] The transcription factor, NF-κB, has also been found to be essential in the activation and recruitment of macrophages as it influences the expression of a number of pro-inflammatory genes. [5,6] Aoki et al [27] demonstrated the activation of NF-κB and expression of downstream genes; these changes seen in the vessel wall of the early stages of aneurysm development in a rat model.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%